2018
DOI: 10.1155/2018/2484036
|View full text |Cite
|
Sign up to set email alerts
|

Successful Spontaneous Pregnancy after Treatment for Ewing Sarcoma including Sacrectomy

Abstract: Ewing sarcomas are highly malignant bone tumors and usually occur in childhood. Radiation therapy, chemotherapy, and surgical methods increase the survival rate of the affected patient, but infertility and reduced reproductive capacity are common late effects of pediatric cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…4 We found that the caesarean birth rate was higher compared with other series. 10 38 39 Among women seeking elective cesarean birth, reasons included perceived physical joint limitations in hips, pelvis, and abdomen. 4…”
Section: Discussionmentioning
confidence: 99%
“…4 We found that the caesarean birth rate was higher compared with other series. 10 38 39 Among women seeking elective cesarean birth, reasons included perceived physical joint limitations in hips, pelvis, and abdomen. 4…”
Section: Discussionmentioning
confidence: 99%
“…31 The safety of chemotherapy during pregnancy is based upon a few case series and not all multiagent regimens have been studied in detail. 32 33 A 10-year retrospective study in Belgium focusing in pregnant women with cancer, prenatally exposed to cytotoxic treatment, demonstrated that more than 50% of neonates were admitted to the neonatal intensive care unit due to preterm labor. 9…”
Section: Discussionmentioning
confidence: 99%
“…Метастазы в тканях головы и шеи встречаются в 12,5%, а в центральной нервной системе -в 10-37% случаев [11]. Инвазивный рост опухоли в окружающие мягкие ткани [23] вовлекает в патологический процесс регионарные лимфатические узлы (поражаются в 5-15% случаев) [2]. До применения системной терапии метастазы развивались почти у 90% больных [8].…”
Section: метастазированиеunclassified
“…Успешное применение хирургического лечения и послеоперационной лучевой терапии в сочетании с хи миотерапией значительно повысило выживаемость больных с саркомой Юинга. Так, в 1960-х годах примерно половина пациентов умирала в течение первого года с момента установления диагноза, двухлетняя выживаемость составляла всего 21% [23,44]. В настоящее время общая пятилетняя выживаемость составляет 53-75% [22,42,45], хотя имеются сообщения о 5-и 10-летней выживаемости на уровне 84 и 74% соответственно [12,27].…”
Section: лечениеunclassified